The Economic Determinants of Foreign Exchange Reserve Fluctuations in Indonesia - Dea Rustami; Septriani Septriani (Future Science, 2024)
This research examines the economic factors that drive fluctuations in Indonesia’s foreign exchange reserves, concentrating on external debt, global trade activities (exports and imports), and the exchange rate of the Rupiah against the US Dollar. By utilizing secondary data obtained from the World Bank, the research applies multiple linear regression analysis through EViews 12 to assess the influence of these critical variables on foreign exchange reserves. The findings reveal a significant correlation between external debt, exports, and imports with changes in foreign exchange reserves, whereas the exchange rate shows no notable influence. The regression model accounts for 95.81% of the variation in Indonesia’s foreign exchange reserves, underscoring external debt, exports, and imports as pivotal factors, while the exchange rate plays a relatively minor role. These insights are crucial for policymakers aiming to ensure economic stability.